Assessing the Knowledge Levels of Farmers on Paddy Straw Management Techniques as the Survey Based Approach in Central Region of Uttar Pradesh - Arvind Kumar; R. K. Doharey; N. R. Meena; Gaurav Kumar; Anurag Dixit; Aman Verma (The Bioscan, 2025)
This Study the knowledge level on Perception of Farmers towards paddy straw management techniques in Central Region of Uttar Pradesh, particularly study was conducted in four districts namely; Lakhimpur Kheri, Barabanki, Kanpur Dehat and Kanpur Nagar during 2024-2025, 320 paddy farmers selected from each district, two blocks were selected randomly. Thus, total numbers of eight blocks were selected for the study area. From each block, four villages were selected randomly. Thus, total numbers of thirty two villages were selected for the study. From each village, ten farmers were selected randomly. The study aimed to knowledge levels of various practices related to paddy straw management techniques of mulching, animal fodder, mushroom farming, biofuel and implements paddy straw chopper, zero tillage seed drill, baler etc. The results revealed a generally medium knowledge level for Paddy Straw Management Techniques and implements. Thus, total three hundred twenty farmers were selected and personally interviewed with the help of well-structured schedule. The study was knowledge of farmers related to paddy straw management techniques. Thus the concluded majority of the respondents had medium level (59.68%) of knowledge about paddy straw management technique, (23.13%) were in the low category and (17.19%) were classified in the high category.